PENDAMPINGAN PROGRAM PEMBERDAYAAN KESEHATAN MASYARAKAT TERHADAP COVID-19 MELALUI KOMUNITAS KADER POSYANDU DELIMA DI DESA GLANGGANG - Siti Yumnah (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2021)
Health empowerment programs in the community currently need to be socialized so that the community can understand and maintain their respective health conditions. We are currently being tested with the emergence of coronavirus or cOVID-19 disease outbreak that first appeared in December 2019 in China and then spread in Indonesia last March. Implementing community health empowerment programs carried out by the Posyandu Delima cadre community in Sentono Sub-district of Glanggang has carried out community health empowerment programs well, such as clean and healthy behavior programs, mask making counseling, and immunization programs for toddlers. The purpose of this community service help is to educate all people to always maintain health by doing a clean and healthy lifestyle, by always maintaining the cleanliness of the environment and doing sports in the morning. Kata Kunci : Community Health Empowerment Program, Posyandu Delima Cadre Community, Sentono Sub-Village Glanggang.